Murdoch's world : the last of the old media empires - Folkenflik, David (PublicAffairs, 2013)
Rupert Murdoch is the most significant media tycoon the English-speaking world has ever known. No one before him has trafficked in media influence across those nations so effectively, nor has anyone else so singularly redefined the culture of news and the rules of journalism. In a stretch spanning six decades, he built News Corp from a small paper in Adelaide, Australia into a multimedia empire capable of challenging national broadcasters, rolling governments, and swatting aside commercial rivals. Then, over two years, a series of scandals threatened to unravel his entire creation.<BR.